Pengembangan Media Video Pembelajaran Berbasis Doratoon Pada Materi Pancasila & Pandangan Hidup Bangsa Kelas VIII SMP Negeri 3 Kabupaten Sorong - Herni Paulina Fadimpo; Indri Anugrah Rahmadhani; Sahiruddin Sahiruddin (Institut Nalanda, 2024)
Various educational video media are not used at SMP Negeri 3 Sorong Regency. The objective of this study is to create educational video media based on Doratoon that is both valid, practical, and effective for instructional purposes. Employing a research and development (R&D) methodology, the study utilizes the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data gathering techniques consist of observing, conducting interviews, documenting, and employing data collection instruments. The participants in this study were 24 eighth-grade students from SMP Negeri 3 in Sorong Regency. The validation results for the development of Duratone-based educational video media were obtained through reviews by material and media experts with an average material percentage of 97% and an average media percentage of 86% meeting the